PENGGUNAAN KAIDAH FIQHIYYAH “AL-KHURŪJ MIN AL-KHILĀF MUSTAHAB” TERKAIT BAB IBADAH DALAM KITAB I’ĀNAT AL THĀLIBĪN - Lathifah Munawaroh (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2017)
This paper is trying to describe the rules of jurisprudence "Al-Khurūj Min al-Khilāf  Mustahab " used by Sayyid Bakri in his book named I'ānat al Thālibīn which is the explaination of book Fath al-Mu'īn. This is quite important, especially in ethics in khilafiyah problems that occur in the chapters of jurisprudence as well as in order to carry prudence in religion. Precautions for cases that still in the difference of jurisprudence is ordered. In fact, it is said that including the shubhat cases are cases that occur differences in jurisprudence. Of course the rules of " Al-Khurūj Min al-Khilāf  Mustahab " can not be applied absolutely unconditionally. However, in practice the scholars define a few terms, so that not all differences are mu'tabar and encouraged to get out of that difference.One of the unique that Sayyid Bakri did in this book, he used it in strengthening his opinion, and this paper only discusses how Sayyid Bakri use the rules of jurisprudence " Al-Khurūj Min al-Khilāf Mustahab ". This paper limits its application to the chapter Worship only: prayer , fasting, zakat and hajj.